2010
DOI: 10.1002/ppul.21201
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory impedance and response to salbutamol in asthmatic Vietnamese children

Abstract: There is a high incidence of pediatric asthma in Vietnam, but little lung function data are available. The aim of the study was to compare respiratory resistance (Rrs), reactance (Xrs), and responses to salbutamol between asthmatic and healthy primary school children in Hanoi. Because respiratory mechanics vary along the breathing cycle, measurements were assessed separately in inspiration (Rrsi, Xrsi) and expiration (Rrse, Xrse).Inpatients with doctor-diagnosed asthma were measured 2-3 days following admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…Knowing the reference equation it is possible to detect abnormal lung function and, as previously mentioned, FOT can then be used in the follow-up of children with lung diseases such as asthma, neonatal chronic lung disease, or cystic fibrosis or asthma. 5,[7][8][9][13][14] The reference equations calculated from the healthy Italian children in the present study are very similar to those published by Hall et al 18 from Australian children Pediatric Pulmonology 18 to calculate Z-scores for Italian children and comparing them with Z-scores calculated using the Italian equations from the present study, no Pediatric Pulmonology Fig. 2.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Knowing the reference equation it is possible to detect abnormal lung function and, as previously mentioned, FOT can then be used in the follow-up of children with lung diseases such as asthma, neonatal chronic lung disease, or cystic fibrosis or asthma. 5,[7][8][9][13][14] The reference equations calculated from the healthy Italian children in the present study are very similar to those published by Hall et al 18 from Australian children Pediatric Pulmonology 18 to calculate Z-scores for Italian children and comparing them with Z-scores calculated using the Italian equations from the present study, no Pediatric Pulmonology Fig. 2.…”
Section: Discussionsupporting
confidence: 75%
“…The similarities in BDR despite the substantial difference in salbutamol dose show that 200 mg is sufficient for healthy children and likely reflects a relatively flat dose-response curve in such children. Other studies have reported similar changes in lung function following bronchodilatation measured with FOT in asthmatic children 13 or with different wheezing phenotypes. 14 In conclusion, the data from the present study give the reference equation for R rs and X rs for Italian children between 2 and 6 years of age.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…5 This 12% criterion, which was recently reaffirmed in a large international study, 6 approximates the 95th percentile for percentage change in FEV 1 after bronchodilator administration in general population studies, which mainly consist of adults. 7 The forced oscillation technique, which provides information on airway resistance and reactance, has also been used to measure response to bronchodilators and to differentiate between asthmatic and nonasthmatic patients, 8,9 especially in younger children who are unable to cooperate during spirometric testing. However, this technique is not widely used because standardized guidelines are lacking.…”
mentioning
confidence: 99%
“…FOT makes it possible to distinguish children with asthma from healthy children by assessing the initial parameters of the FOT as well as the results of the assessment of reversibility of the airway obstruction test [7,[21][22][23][24].…”
Section: Fot In Obstructive Airway Diseases In Childrenmentioning
confidence: 99%